Social Construction of Gender Motives in the Sidodadi Community in Sidoarjo Regency - Rahma Safitriana; Agus Machfud Fauzi; Ahmad Ridwan (Jurnal Partisipatoris, 2026)
The social construction of gender in rural communities not only shapes the division of roles between men and women but also underlies the motives behind various social and economic actions. This study aims to analyze the social construction of gender motives in the Sidodadi community, Sidoarjo Regency, focusing on normative reasons, economic drivers, and social interests that influence individuals in performing gender roles. This research employs a qualitative approach with a descriptive-analytical design. The informants consisted of five families, comprising married couples aged 28–52 years, selected using purposive sampling based on their involvement and experience in gender role practices. Data were collected through in-depth interviews and observations of the informants’ social and economic activities, and were analyzed using thematic analysis. The findings indicate that normative motives serve as the primary basis for the division of gender roles, which are perceived as natural and transmitted across generations. However, economic pressures encourage flexibility in gender roles, particularly through women’s involvement in informal economic activities and home-based businesses as strategies to maintain household economic stability. In addition, social interests shape gender-based actions as efforts to maintain household harmony and gain social acceptance within the community. This study concludes that gender motives in the Sidodadi community are the result of a dynamic and contextual process of social construction, formed through the interrelation of social norms, economic conditions, and social interests. These findings are expected to enrich gender sociology studies based on local contexts and contribute empirically to the development of gender studies in rural communities